Diversity and Antifungal Activity of Actinomycetes Symbiont Hard Coral Mucus of Genera Goniopora and Porites - Riyanti,; Nurkhasanah, Wulan; Radjasa, Ocky Karna (UI Scholars Hub, 2016)
Screening new bioactive compounds from marine actinomycete organisms associated with corals (Goniopora and Porites) can be an alternative method to discover the natural antifungal compounds. This study aims to determine the density and diversity of actinomycete symbionts based on repetitive sequence-based-polymerase chain reactions (rep-PCR) and to discern the ability of antifungal activity of isolates symbiotic with hard coral mucus by using a pour plate method. A total of 143 isolates were obtained from the hard coral mucus of genera Goniopora and Porites. High genetic diversity was observed among the isolates. Ten isolates with different morphological characteristics were selected to extract its secondary metabolites and then followed by an antifungal test. The isolate with the code of SCAS324 was the one with the antifungal activity, marked by the formation of a very strong inhibition zone of 54.7±0.4 mm toward Aspergillus flavus and 49.2±2.7 mm toward Candida albicans. Antifungal screening showed that the antifungal activity of the isolate SCAS324 was three times as effective as the commercial antifungal.